Hydroxypropyl-β-cyclodextrin as an effective carrier of curcumin - piperine nutraceutical system with improved enzyme inhibition properties - Anna Stasiłowicz; Ewa Tykarska; Kornelia Lewandowska; Maciej Kozak; Andrzej Miklaszewski; Joanna Kobus-Cisowska; Daria Szymanowska; Tomasz Plech; Jacek Jenczyk; Judyta Cielecka-Piontek (Taylor & Francis Group, 2020)
The nutraceutical system of curcumin-piperine in 2-hydroxypropyl-β-cyclodextrin was prepared by using the kneading technique. Interactions between the components of the system were defined by X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC), infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR). Application of hydroxypropyl-β-cyclodextrin as a carrier-solubiliser improved solubility of the curcumin-piperine system, its permeability through biological membranes (gastrointestinal tract, blood-brain barrier) as well as the antioxidant, antimicrobial and enzyme inhibitory activities against acetylcholinesterase and butyrylcholinesterase.